2019
DOI: 10.1007/s11095-019-2705-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Biological Activity of E. coli Derived Soluble and Precipitated Bone Morphogenetic Protein-2

Abstract: Purpose: There is a plethora of studies on recombinant human bone morphogenetic protein-2 (rhBMP-2) application and delivery systems, but surprisingly few reports address the biophysical properties of the protein which are of crucial importance to develop effective delivery systems or to solve general problems related to rhBMP-2 production, purification, analysis and application. Methods:The solubility, stability and bioactivity of rhBMP-2 obtained by renaturation of E. coli derived inclusion bodies was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…Some authors have reported differing BMP‐2 release rates in PBS compared to cell culture medium or serum (Ruhé et al, 2006; Strobel, Bormann, Kadow‐Romacker, Schmidmaier, & Wildemann, 2011). BMP‐2 has an isoelectric point of 8.5 (Uludag, D'Augusta, Palmer, Timony, & Wozney, 1999) and its solubility is extraordinarily dependent on ionic strength and pH (Quaas et al, 2019). Given the extremely poor solubility of BMP‐2 in PBS‐based buffers, there is a risk of release results being influenced by solubility‐ and aggregation‐dependent recovery effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have reported differing BMP‐2 release rates in PBS compared to cell culture medium or serum (Ruhé et al, 2006; Strobel, Bormann, Kadow‐Romacker, Schmidmaier, & Wildemann, 2011). BMP‐2 has an isoelectric point of 8.5 (Uludag, D'Augusta, Palmer, Timony, & Wozney, 1999) and its solubility is extraordinarily dependent on ionic strength and pH (Quaas et al, 2019). Given the extremely poor solubility of BMP‐2 in PBS‐based buffers, there is a risk of release results being influenced by solubility‐ and aggregation‐dependent recovery effects.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation, refolding, and purification of dimeric non‐glycosylated rhBMP‐2 was performed by refolding of rhBMP‐2 from inclusion bodies (IBs) produced in Escherchia coli and subsequent purification as previously described (Quaas et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-(N-morpholino) ethanesulfonic acid (MES; ≥ 99%) was purchased from Carl Roth, Karlsruhe, Germany. E. coli derived recombinant human bone morphogenetic protein 2 (rhBMP-2), simply referred to as BMP-2 in the following, was produced at the Institute for Technical Chemistry, Leibniz Universität Hannover, Hannover, Germany, as previously described [22].…”
Section: Methodsmentioning
confidence: 99%
“…BMP-2 has an isoelectric point (pI) of about 8.5 after chaotropic denaturation [21] and the tendency to form redissolvable aggregate particles of native protein with a pI of 7.7-8.3 at physiologic ionic strength and pH [22,23]. We were interested in the potential influence of poor BMP-2 solubility in physiological buffers like PBS [24] on the outcome of in vitro release tests.…”
Section: Introductionmentioning
confidence: 99%